The challenges of corporate entrepreneurship in the disruptive age - Kuratko, Donald F.; Hoskinson, Sherry (Advances in the study of entrepreneurship, innovation, and economic growth ;, 2018)
The new disruptive age in technology has presented a strategic game changer for most organizations. The severe modifications in complete industries and unpredictable market conditions have created significant challenges for simple organizational survival, let alone providing an avenue for growth, innovation, and new ventures. These conditions have fostered a greater need for corporate innovative activities and a better understanding of the corporate entrepreneurial process within such an environment.This volume focuses on the greatest challenges that exist in Corporate Entrepreneurship in this disruptive age, and explores the complications posed by the dynamic environment that all organizations of today are forced to confront. It addresses the need for a better understanding of the role of external socio-cultural, economic and market conditions upon the managerial and leadership decisions and actions in pursuit of Corporate Entrepreneurship strategies.